Bee & Flea and the compost caper - Humphrey, Anna (Owlkids Books, 2022)
"Bee is buzzing along--busy, but bored--when Flea rides in on a dog's back and changes her life forever. Flea is the one and only agent of the Fenced-in-area Law Enforcement Agency (the F.L.E.A. for short) and she's heard about trouble in the compost heap: word is, it has erupted into a wild frenzy, and she needs to investigate. Turns out Bee has something Flea needs: wings. So together they fly off to the scene of the crime. Once Bee puts on her F.L.E.A.-issued glasses, she sees that the compost heap is in chaos. Bacteria are bopping, critters are surfing down slime, and mites are playing a game of dodge-poop, all while Flea tries to command order. But even as she dismisses Bee to garbage duty, Bee is making her own notes. And just when Bee is about to give up, she has an epiphany... Maybe the compost chaos isn't that at all. Maybe all the excitement and, yes, pooping is about making fresh, fertile soil for the garden! But can Flea accept that her services aren't needed here? And will Bee earn her F.L.E.A. badge... or will she go back to pollinating dandelion, after dandelion, after dandelion? Peppered throughout with (approx.. 30) lively black and white illustrations by Mike Deas, this book is a fun romp through the compost heap, with tons of real-life nature facts (and a quiz in the backmatter) to help kids learn about all the tiniest composting critters (rotifers, potworms, mites, bacteria) The first book in a series featuring the unlikely pair of the eager-to-learn Bee and the brash but well-meaning Flea."--